2015 IEEE International Ultrasonics Symposium (IUS) 2015
DOI: 10.1109/ultsym.2015.0283
|View full text |Cite
|
Sign up to set email alerts
|

RSNA QIBA ultrasound shear wave speed Phase II phantom study in viscoelastic media

Abstract: Using ultrasonic shear wave speed (SWS) estimates has become popular to noninvasively evaluate liver fibrosis, but significant inter-system variability in liver SWS measurements can preclude meaningful comparison of measurements performed with different systems. The RSNA Quantitative Imaging Biomarker Alliance (QIBA) ultrasound SWS committee has been developing elastic and viscoelastic (VE) phantoms to evaluate system dependencies of SWS estimates. The objective of this study is to compare SWS measurements bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 6 publications
2
52
0
Order By: Relevance
“…Previous elastic phantom studies demonstrated inter-system variability ranging from 6 -12 % in elastic phantoms with a nominal SWS of 1.0 and 2.0 m/s [7]. In visco-elastic phantoms that more accurately simulate the liver, the median SWS estimates for the greatest outliers in each phantom/focal depth combination ranged from 12.7 -17.6 % [8].…”
Section: Introductionmentioning
confidence: 96%
“…Previous elastic phantom studies demonstrated inter-system variability ranging from 6 -12 % in elastic phantoms with a nominal SWS of 1.0 and 2.0 m/s [7]. In visco-elastic phantoms that more accurately simulate the liver, the median SWS estimates for the greatest outliers in each phantom/focal depth combination ranged from 12.7 -17.6 % [8].…”
Section: Introductionmentioning
confidence: 96%
“…Their results suggest a bias in elastic property estimation which varies with each quantitative modality and highlights the difficulty in finding a reference method to assess the elastic properties. In [13] and [14], inter-laboratory studies of SWS estimation were performed in elastic and viscoelastic phantoms, respectively. These studies found a significant difference among measurements at different depths.…”
Section: Introductionmentioning
confidence: 99%
“…Working on elastic phantoms, a statistically significant difference in the SWS estimates among systems and depth of measurement in the phantom was shown, whereas no statistically significant differences were found among operators using the same or equivalent systems under the same conditions [129]. Similar results were obtained using phantoms with viscoelastic properties similar to those observed in normal and fibrotic liver [130]. The measurements were performed at multiple focal depths (3.0, 4.5 and 7.0 cm).…”
Section: Studies On Phantomsmentioning
confidence: 55%